A comparative study on efficacy and safety of modified partial stapled hemorrhoidopexy versus conventional hemorrhoidectomy: a prospective randomized controlled trial - Tae Gyu Kim; Chul Seung Lee; Dong Geun Lee; Choon Sik Chung; Seung Han Kim; Sang Hwa Yu; Jeong Eun Lee; Gwan Cheol Lee; Dong Woo Kang; Jeong Sub Kim; Gyu Young Jeong (Annals of Coloproctology)
Purpose The long-term outcomes and efficacy of partial stapled hemorrhoidopexy (PSH) compared with those of conventional hemorrhoidectomy (CH) are not fully understood. This study aimed to introduce a modified PSH (mPSH) and compare its clinical efficacy and safety with those of CH. Methods A prospective randomized controlled trial was conducted. This study was performed at a single hospital and involved 6 colorectal surgeons. In total, 110 patients were enrolled between July 2019 and September 2020. Patients were randomly assigned to undergo either mPSH group (n=55) or CH group (n=55). The primary outcome was to compare postoperative average pain and postoperative peak pain using visual analog scale score between the 2 groups. Results The required duration of analgesia was shorter in the mPSH group than in the CH group, although the difference was not statistically significant (P=0.096). However, the laxative requirement duration (P<0.010), return to work (P<0.010), satisfaction score (P<0.010), and Vaizey score (P=0.014) were significantly better in the mPSH group. The average and peak postoperative pain scores were significantly lower in the mPSH group during the 15 days after surgery (P<0.001). The overall complication rate in both groups was 9.1%, with no significant difference between the groups (P=0.867). Conclusion The mPSH group demonstrated better improvement in symptoms, lower pain scores, and greater patient early satisfaction after surgery than the CH group. Therefore, this surgical technique appears to be a safe and effective alternative for CH.